Management controls in an apparel group: an institutional theory perspective. Issue 2 (8th May 2017) - Doluwarawaththa Gamage, Sujeewa Damayanthi; Gooneratne, Tharusha
Abstract : Purpose: The purpose of this paper is to explore how management controls in an organization take shape amidst the tensions between external institutional forces and the internal dynamics arising from the different powers and interests of managers as well as from intra-organizational norms, rules and taken-for-granted assumptions. Design/methodology/approach: Adopting an interpretivist stance, this study employs the embedded (nested) case study approach drawing evidence from an apparel group which consists of a head office and four clusters. Theoretically, the paper is informed by institutional theory, and particularly draws on concepts such as organizational field, ceremonials, rational myths, isomorphism, institutional logics and loose coupling. It is further complemented by strategic responses of Oliver (1991), as well as materials and discursive elements in elaborating how external pressures influence control practices of an organization, and how internal actors strategically respond to those pressures in balancing external legitimacy and internal efficiency requirements. Findings: The field-study findings reveal that management controls of the case-study organization have taken shape amidst external pressures, specifically from customers and internal dynamics such as interests of key actors, who strategically respond to external pressures and head -office specifications. Research limitations/implications: Situating management controls within external pressures and internal dynamics, the findings of this study have implications for research on organizational heterogeneity, and it offers learning points for managers in formulating management controls by balancing conflicting internal and external pressures. Practical implications: In reality, practicing managers are faced with conflicting logics arising from external pressures and internal dynamics stemming from different power- and interest-holding managers as well as intra-organizational norms, rules and taken-for-granted assumptions in their everyday encounters in organizations. This study provides some pointers for such practicing managers in designing and implementing management control systems by effectively balancing these opposing influences and formulating systems suited to the circumstances of a particular organization. Originality/value: Moving beyond the widely held narrow conceptualization of institutional theory akin to (external) isomorphism and organizational conformity, this paper brings out organizational heterogeneity through the active agency of actors in terms of their power, interest and proclivities as well as their use of organizational norms and rules in responding to such external institutions.